ADVANCED TREATMENT OF PRIMARY PULMONARY TB IN HILDREN WITH IMPAIRED GROWTH AND DEVELOPMENT WITH THE MOTHER AS THE BREADWINNER AND AS A DIRECT THERAPY OBSERVER - Aprilia Elisabet (Fakultas Kedokteran Universitas Lampung, 2014)
Tuberculosis (TB) is an infectious disease that cause of death in high mortality and morbidity, and long-term therapy in the world. In Indonesia, TB is a major cause of mortality and morbidity in children after a respiratory infection. The objective in this clinical study is to identificatify of internal and external factors of a patient with pulmonary tuberculosis with impaired growth and development with the mother who became the breadwinner of the family and also as direct therapy observer. The methods in this clinical study is descriptive study using primary data were obtained through alloanamnesis, physical examination, advancedexamination, home visit, collecting family, psychosocial, and environment data. The results is a girl with age under five years with impaired growth and development that have a history of exposure to TB patients whose the mother is not only as breadwinner but also as direct therapy observer. Therapy of this patient are Rifampisin 1x150 mg and INH 1x100 mg, high calory and high protein diet, sunlight therapy, speech therapy and mother’s care. After treatment, complaints reduced, growt and development improved. The conclusion is pulmonary TB in children can indeed cause growth disorders so as a doctor must quick and active in pulmonary TBmanagement. [J Agromed Unila 2014; 1(3):268-273]Keywords: disorders of growth and development, family medicine, pulmonary tuberculosis